From biopolitics to ethopolitics: Foucault and us (Nóema, 2013)
Foucault's category of the "society of normalization" is no longer apt to grasp the functioning of contemporary societies. The logic and mathematics of normalization have been replaced by the logic and mathematics of optimization. Such a historical passage marks the birth of ethopolitics.
Keywords: Standardization; optimization; Surveillance Society; efficiency; ethopolitics